Global Dynamics of Three Anticompetitive Systems of Difference Equations in the Plane - M. DiPippo; M. R. S. Kulenović (Discrete Dynamics in Nature and Society)
We investigate the global dynamics of several anticompetitive systems of rational difference equations which are special cases of general linear fractional system of the forms ., where all parameters and the initial conditions are arbitrary nonnegative numbers, such that both denominators are positive. We find the basins of attraction of all attractors of these systems.